Spatial scales effects on the geographical origin identification of PGI kiwifruit by stable isotope and mineral elemental fingerprinting - Jiali Li; Jianping Qian; Qian Chen; Zihan Liu; An Li; Xintao Lin; Boyu Shuai; Jiangmin Zhou; Junyi Wang; Zihan Bian; Linghuan Ouyang; Ming Li (Food Control, 2027)

Structural characterization of novel polysaccharides from Sargassum fusiforme with dual anticoagulant activity targeting thrombin and antithrombin III - Yue Zhu; Yuanlin Luo; Yunqin Shi; Jiahui Shao; Shunhao Lin; Xiuting Zhang; Yu Tang; Xiangwei Zhao; Jianping Jiang; Zhenzhong Yang (Food Chemistry, 2026)

Development of a frost-specific module and its integration into a process-based model for winter wheat frost damage simulation - Yuanda Zhang; Peijuan Wang; Yuping Ma; Lin Cheng; Yang Li; Dianchen Han; Dingrong Wu; Shuxian Liu; Jianping Guo (Agricultural and Forest Meteorology, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Nonlinear prestack inversion method for the effective pore-fluid bulk modulus based on the Zoeppritz equations - Lin Zhou; Jingye Li; Jianping Liao; Xiaohong Chen; Tong Zhang; Ming Ouyang (Journal of Applied Geophysics, 2026)

Soil nutrient effect on microbial diversity and community composition is modulated by soil aggregate fractions in Yuanjiang savanna, China - Jinxiu Zhang; Zihao Guo; Can Wang; Na Lin; Chunyu Hou; Yajun Chen; Meiyan Zhang; Jianping Wu (Applied Soil Ecology, 2026)

The convergence of food-derived bioactive peptides and organoids: model construction, application, challenges and outlooks - Haowen Chen; Shuguang Wang; Jianping Wu; Jing Chen; Shulong Cai; Rong Xu; Jucai Xu; Lin Zheng; Mouming Zhao (Trends in Food Science & Technology, 2026)

Acid-resistant ferrihydrite-spent grain composites for enhanced as and Sb removal from acid mine drainage - Zhongqiang Hu; Zhan Yao; Lin Yu; Jianping Guo; Zhihui Yang; Weichun Yang; Qi Liao; Xi Chen; Shuyan Mi (Environmental Research, 2026)

Laser-induced hybrid interphase for corrosion dispersion toward durable metal–polymer interfaces in marine environment - Shuangshuang Li; Man Gu; Hailang Wan; Jianping Lin (Chemical Engineering Journal, 2026)

Advanced wick design in solar multistage distillation for on-site water recycling and salt recovery during saline soil remediation - Canjie Lin; Chao Wang; Yang Liu; Changting Wang; Ziwei Liao; Yuyou Lin; Tingting Zheng; Jinjuan Chen; Bolun Peng; Jianping Cao; Bei Liu; Lingyue Zhang; et al. (Chemical Engineering Journal, 2026)

Erratum to: Artemisinin analogue SM934 protects against lupus-associated antiphospholipid syndrome via activation of Nrf2 and its targets - Zemin Lin; Yuting Liu; Li Chen; Shiqi Cao; Yueteng Huang; Xiaoqian Yang; Fenghua Zhu; Wei Tang; Shijun He; Jianping Zuo (Science China Life Sciences, 2026)

Deciphering the shift in extreme precipitation over the lower reaches of the Yangtze River Basin: a synoptic-scale analysis - Jiao Li; Yang Zhao; Jianping Li; Lianyi Guo; Cheng Shen; Lujia Zhang; Lin Deng; Dandan Chen (Climate Dynamics, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

Surface functionalization of water transportation management yarns for bioinspired humidity sensors - Du Nie; Shuyu Zhang; Yaoxian Zheng; Xinling Hu; Jitian Chen; Zijian Yan; Jianping Zhou; Liyun Ma; Naibo Lin (Chemical Engineering Journal, 2026)

SNX25-mediated regulation of NGF by Periploca sepium periplosides from Xiangjiapi in macrophage-dependent anti-nociception - Yuan Chang; Mengru Guo; Wenlong Yuan; Yong Hu; Fenghua Zhu; Xiaoqian Yang; Weimin Zhao; Dongyi He; Shijun He; Jianping Zuo; Zemin Lin (Science China Life Sciences, 2026)

Molecular characterization of a novel partitivirus from quinoa (Chenopodium quinoa) in China - Wenqi Mao; Jiajia Lin; Zhongtian Xu; Penghuan Rui; Xinxin Fang; Hongying Zheng; Yuwen Lu; Jianping Chen; Fei Yan; Guanwei Wu (Archives of Virology, 2026)

Design and research of a grass carp vaccination machine based on enhanced YOLOv8s - Chen Li; Umar Abdulbaki Danhassan; Lin Luo; Songming Zhu; Jianping Li; Zhangying Ye (Aquaculture International, 2026)

Food-derived bioactive peptides: health benefits, structure–activity relationships, and translational prospects - Hongda Chen; Jiabei Sun; Haolie Fang; Yuanyuan Lin; Han Wu; Dongqiang Lin; Zhijian Yang; Quan Zhou; Bingxiang Zhao; Tianhua Zhou; Jianping Wu; Shanshan Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Virtual screening and experimental validation of small-molecule compounds targeting AR in prostate cancer - Zhongqiang Fan; Xuexue Hao; Weiren Chen; Zhunan Xu; Qihua Wang; Muwei Li; Hao Zhang; Congzhe Ren; Yutong Chen; Jianping Lin; Xiaoqiang Liu (Molecular Diversity, 2025)

Crop sample prediction and early mapping based on historical data: Exploration of an explainable FKAN framework - Feifei Cheng; Bingwen Qiu; Peng Yang; Wenbin Wu; Qiangyi Yu; Jianping Qian; Bingfang Wu; Jin Chen; Xuehong Chen; Francesco N. Tubiello; Piotr Tryjanowski; Viktoria Takacs; et al. (Computers and Electronics in Agriculture, 2025)

The effect of vessel noise on behavior and physiology of orange-spotted grouper (Epinephelus coioides) under conditions with and without artificial lighting - Hui Liu; Zijian Lu; Pingping Shen; Kaicheng Zhang; Geng Qin; Jianping Yin; Qiang Lin; Huixian Zhang (Marine Pollution Bulletin, 2025)

Polyacrylonitrile (PAN) electrospun nanofibrous membrane for removing indoor gaseous phthalates: A health-driven framework for macro-channel adsorption module design and its implications - Yu Sun; Donghui Mo; Lvyan Lin; Hongyi Wang; Jianping Cao; Zhongming Bu (Journal of Hazardous Materials, 2025)

Flame-retardant three-dimensional polyvinyl alcohol/microcrystalline cellulose/graphene oxide composite for fire alarm system - Qiuping Wu; Lin Dai; Junjing Ma; Xinyi Wang; Shuangquan Yao; Chengrong Qin; Jianping Sun; Shaohong Shi; Jingru Liu; Zhanhui Yuan; Chuanling Si (Chemical Engineering Journal, 2025)

Grass-legume polyculture enhances plant productivity and nutrient availability by modulating soil enzymatic activities and microbial communities in grassland - Jawad Ali Shah; Chunyu Yue; Yi Xiong; Na Lin; Jianping Wu (Journal of Soils and Sediments, 2025)

Multiple probiotic effects of Ligilactobacillus murinus strain S27 on large yellow croaker (Larimichthys crocea): Promoting growth, improving intestinal health, and enhancing resistance against Pseudomonas plecoglossicida - Zhixin Lin; Jianping Zeng; Yu Zhai; Yuan Shi; Xinhua Chen (Aquaculture, 2025)

Detoxification of thallium from lithium smelting slag by reductive acid leaching - Lin Yu; Siying Zhao; Jianping Guo; Mengying Si; Qi Liao; Yunyan Wang; Qingzhu Li; Zhihui Yang; Weichun Yang (Waste Management, 2025)

Break-off and stagnation of the subducting Nazca slab in the mantle transition zone beneath West-Central South America - Kailun Ba; Jianping Huang; Youqiang Yu; Jianguo Song; Sanzhong Li; Cong Shen; Lin Liu (Tectonophysics, 2025)

Simulating vegetation potential and quantifying uncertainty for precision forestation in arid regions - Jia Qu; Zirui Gai; Qi Liu; Dongwei Gui; Xinlong Feng; Jianping Zhao; Tao Lin; Yunfei Liu; Qian Jin; Zeeshan Ahmed (Remote Sensing Applications: Society and Environment, 2025)

Construction of a molecularly imprinted electroluminescence sensor for pyrimethanil detection via dummy template imprinting combined with click-chemical labeling of mimic enzymes - Lijuan Lin; Peng Gao; Minjin Wu; Kui Luo; Jianping Li (Analytica Chimica Acta, 2025)

Habitat‐Forming Species: Buffers or Amplifiers for Mutualistic Organisms in Response to Climate Change? - Junmei Qu; Zhixin Zhang; Shaobo Ma; Yaqi Wang; Xiaoyu Tang; Jianping Yin; Geng Qin; Qiang Lin (Journal of Biogeography, 2025)
Aim Habitat‐forming species play a critical role in coral reef ecosystems by creating complex physical structures for marine species. Driven by climate change, these habitat‐forming species are undergoing considerable shifts in their geographical distribution, which might trigger cascading effects via protection mutualisms, leading to alterations in the relationships between species. We examined the role of habitat‐forming species in regulating spatial distributions of their mutualistic protectors' influence. Location Global coastal ocean. Methods We used species distribution models to examine how suitable habitats for organisms that form mutualistic relationships with habitat‐forming species respond to climate change, focusing on two representative macrosymbiotic relationships in coral reefs: Coral–coral crab and sea anemone–clownfish. Results The results revealed that corals are more sensitive to climate change than sea anemones, experiencing greater range contractions under projected future conditions. Consequently, the distribution ranges of both coral‐mutualistic crabs and sea anemone‐mutualistic clownfishes are expected to reduce even further when protection mutualisms are considered. Coral crabs are projected to undergo a more rapid range size loss than clownfishes. Main Conclusion These findings highlight the importance of incorporating interspecific interactions among habitat‐forming species into predictions of potential shifts in the biogeographic distributions of mutualistic protectors under climate change.

Behavioral Responses of Migratory Fish to Environmental Cues: Evidence from the Heishui River - Jiawei Xu; Yilin Jiao; Shan-e-hyder Soomro; Xiaozhang Hu; Dongqing Li; Jianping Wang; Bingjun Liu; Chenyu Lin; Senfan Ke; Yujiao Wu; Xiaotao Shi (Fishes, 2025)
Hydropower infrastructure has profoundly altered riverine connectivity, posing challenges to the migratory behavior of aquatic species. This study examined the post-passage migration efficiency of Schizothorax wangchiachii in a regulated river system, focusing on upstream and downstream reaches of the Songxin Hydropower Station on the Heishui River, a tributary of the Jinsha River. We used radio-frequency identification (RFID) tagging to track individuals after fishway passage and coupled this with environmental monitoring data. A Cox proportional hazards model was applied to identify key abiotic drivers of migration success and to develop a predictive framework. The upstream success rate was notably low (15.6%), with a mean passage time of 438 h, while downstream success reached 81.1%, with an average of 142 h. Fish exhibited distinct diel migration patterns; upstream movements were largely nocturnal, whereas downstream migration mainly occurred during daylight. Water temperature (HR = 0.535, p = 0.028), discharge (HR = 0.801, p = 0.050), water level (HR = 0.922, p = 0.040), and diel timing (HR = 0.445, p = 0.088) emerged as significant factors shaping the upstream movement. Our findings highlight that fishways alone may not ensure functional connectivity restoration. Instead, coordinated habitat interventions in upstream tributaries, alongside improved passage infrastructure, are crucial. A combined telemetry and modeling approach offers valuable insights for river management in fragmented systems.

Structure–function relationship of the brown seaweed Undaria pinnatifida laminaran: Protein kinase C-mediated mucus secretion and gut barrier restoration - Kit-Leong Cheong; Lin Chen; Si-Yuan Lu; Amanullah Sabir; Jianping Chen; Zhuo Wang; Suresh Veeraperumal; Jude Juventus Aweya; Xian-Qiang Chen; Saiyi Zhong; Karsoon Tan; A.M. Abd El-Aty (Carbohydrate Polymers, 2025)

Electrochemistry sensing of ascorbic acid based on conductive metal-organic framework (Cu3(benzenehexathiol)) nanosheets modified electrode - Runhao Yuan; Xiaolong Zhong; Weiming Sun; Jian Wang; Chuanhui Huang; Zhenyu Lin; Jianping Zheng (Analytica Chimica Acta, 2025)

Corrigendum to “Redistribution of vocal snapping shrimps under climate change” [Sci. Total. Environ. 954 (2024) 176191] - Junmei Qu; Geng Qin; Hongwei Huang; Shaobo Ma; Qiang Lin; Zhixin Zhang; Jianping Yin (Science of The Total Environment, 2025)

Absorption, transport, blood-brain barrier penetration, and neuroprotection of walnut peptides LR and LPI - Shuguang Wang; Yao Tang; Guowan Su; Lin Zheng; Yongliang Zhuang; Bifen Chen; Hongbing Fan; Mouming Zhao; Jianping Wu (Food Research International, 2025)

Nitrogen-Doped tannin carbon dots anchored NiCo-LDH composites for high-performance asymmetric supercapacitors - Shirui Wang; Jianping Deng; Menghan Li; Jiande Lin; Lu Luo; Zhanhui Yuan; Wenxue Zhang; Cheng He; Guanben Du; Weigang Zhao (Chemical Engineering Journal, 2025)

Microbial strategies regulate organic carbon accumulation in saline paddy soils: A millennium chronosequence - Dan Cao; Xiangxiang Wang; Yi Miao; Chuanfa Wu; Haoqing Zhang; Shuang Wang; Feng Wang; Lin Chen; Chao Liang; Yakov Kuzyakov; Jianping Chen; Tida Ge; et al. (CATENA, 2025)

Peptide-conjugated alginate fiber: A skeletal muscle regenerative scaffold - Yajun Li; Yueren Wu; Tong Wu; Can Zhang; Jianwu Dai; Jianping Tang; Lin Li; Liyang Shi (Carbohydrate Polymers, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Structure optimization of a hydrocyclone for separation of recycled rubber particles with low-density difference - Long Li; Li Dai; Lin Zeng; Penghui Zhou; Jianping Li; Yulong Chang; Tong Zhang; Aosong Wei; Liang Ma; Hualin Wang (Process Safety and Environmental Protection, 2025)

Novel cell factory for the production of 24-epi-ergosterol, an un-natural semi-synthetic precursor for the production of brassinolide in Yarrowia lipolytica - Yuanying Wang; Shuxian Liu; Zeyu Sheng; Yun Feng; Yinmiao Wang; Yiqi Jiang; Li Zhu; Mianbin Wu; Lirong Yang; Jianping Lin (World Journal of Microbiology and Biotechnology, 2025)

Erratum: wet bias of summer precipitation in the northwestern Tibetan Plateau in ERA5 is linked to overestimated lower-level southerly wind over the Plateau - Tinghai Ou; Deliang Chen; Jianping Tang; Changgui Lin; Xuejia Wang; Julia Kukulies; Hui-Wen Lai (Climate Dynamics, 2025)
We sincerely apologize for a technical error revealed in this article, published in 2023: the spectral nudging process at the upper levels was not functioning as intended. Consequently, the final results presented in the original work are based on WRF downscaling without active spectral nudging. To assess the potential impact of this error on the study’s main conclusion, we conducted two additional experiments using the same WRF version 3.7.1. Results show that the technical error does not alter the main conclusion of the study: the ERA5 overestimation of summer precipitation over the northwestern Tibetan Plateau is associated with an overestimated lower-level southerly wind.

The impacts of shrub branch shelter and nitrogen addition on soil microbial activity and plant litter decomposition in a desert steppe - Xiongkui Lin; Rebecca L. Schneider; Stephen J. Morreale; Hongmei Wang; Jianping Li; Zhigang Li (Applied Soil Ecology, 2025)

Canagliflozin reverses doxorubicin-induced cardiotoxicity via restoration of autophagic homeostasis - Jianping Luo; Mingyuan He; Changzhu Liang; Xiaoxia Huang; Yingqi Zhu; Donghong Hu; Junyu Yan; Mingjue Li; Hairuo Lin; Wangjun Liao; Jianping Bin; Ziyun Guan; et al. (Toxicology and Applied Pharmacology, 2025)

Dynamic multi-objective time-temperature management for climacteric fruit cold storage considering ripeness windows and energy consumption - Qian Chen; Jianping Qian; Huibin Li; Xintao Lin; Jiali Li; Zihan Liu; Zhiyao Zhao (Journal of Food Engineering, 2025)

A novel nonlinear prestack inversion method based on nutcracker optimization algorithm with high convergence speed - Lin Zhou; Ming Ouyang; Jianping Liao; Jingye Li; Hanlin Xia; Haiyang Ding (Journal of Applied Geophysics, 2025)

Windfarm construction alters soil multinutrient cycling by destabilizing microfauna community in a mountain ecosystem - Debao Li; Changwei Ma; Chunyu Yue; Na Lin; Yingmo Zhu; Jianping Wu (Journal of Environmental Management, 2025)

Future projections of precipitation extremes over East Asia based on a deep learning downscaled CMIP6 high-resolution (0.1°) dataset - Yi Yang; Hai Lin; Yi Xu; Hang Pan; Guangtao Dong; Jianping Tang (Climatic Change, 2025)

The Genetic Architecture of Local Adaptation and Reproductive Character Displacement in Scutiger boulengeri Complex (Anura: Megophryidae) - Xiuqin Lin; Chaochao Yan; Yuanfei Wang; Sining Huang; Haoqi Yu; Chungkun Shih; Jianping Jiang; Feng Xie (Molecular Ecology, 2025)
Speciation is a continuous process driven by barriers to gene flow. Based on genome‐wide SNPs (single nucleotide polymorphisms) of 190 toads from 31 sampling sites of Scutiger boulengeri complex, we found evidence for monophyly which represented a continuous speciation process of at least six lineages in S. boulengeri , which radiated and exhibited varying degrees of divergence and gene flow. The SNP‐based phylogenetic tree was largely discordant with the multilocus mitochondrial tree (i.e., S. mammatus and S. glandulatus nested in the lineages of S. boulengeri ) published before. The Min Mountains (MM) and Qinghai‐Tibet Plateau (QTP) lineages differ fundamentally in habitat (i.e., elevation) and morphology (i.e., SVL), we detected signatures of potential high‐altitude and cold adaptation genes in QTP (vs. MM). We found the evidence of reproductive trait disparity (i.e., SVL and nuptial pads) is key to promoting sympatric rather than allopatric species pairs. In addition, we identified selection signals for genes related to sympatric character displacement, genes linked to obesity‐related traits, nuptial spines morphology and enlarged chest nuptial pads in S. mammatus (vs. QTP group of S. boulengeri ). Our study provided new insight and paradigm for a varied speciation pattern from local adaptation of allopatry to sympatric character displacement in the S. boulengeri complex.

Redistribution of vocal snapping shrimps under climate change - Junmei Qu; Geng Qin; Hongwei Huang; Shaobo Ma; Qiang Lin; Zhixin Zhang; Jianping Yin (Science of The Total Environment, 2024)

Hydrocyclone-induced classification reduction and spin desorption of contaminated soil remediation with heavy metal and organics - Yi Liu; Jiahui Ren; Kai Ma; Jianping Li; Pengbo Fu; Kuangfei Lin; Hualin Wang (Journal of Hazardous Materials, 2024)

Design and research of the spindle-shaped fish vaccine adsorption injection device - Chen Li; Kang Wu; Musa Abubakar Tadda; Lin Luo; Zhangying Ye; Jianping Li; Songming Zhu (Aquaculture International, 2024)

Emission, distribution and formation characteristics of polybrominated dibenzo-p-dioxins and dibenzofurans during co-disposal of hexabromocyclododecane-containing waste in cement kiln - Jian Wang; Bingcheng Lin; Xiao Wang; Guorui Liu; Rong Jin; Jukun Xiong; Jianping Guo; Yinming Li; Minghui Zheng (Science of The Total Environment, 2024)

TaSRT2 recognizes a viral protein to activate host immunity by increasing histone acetylation - Kaili Zhong; Yaoyao Jiang; Haichao Hu; Bowen Yuan; Mila Wu; Aizhu Tu; Gecheng Xu; Linna Cai; Tingting Liu; Shiqi Gao; Linzhi Li; Qiansheng Liao; et al. (Science Bulletin, 2024)

Deficit irrigation combined with a high planting density optimizes root and soil water–nitrogen distribution to enhance cotton productivity in arid regions - Fengquan Wu; Qiuxiang Tang; Jianping Cui; Liwen Tian; Rensong Guo; Liang Wang; Zipiao Zheng; Na Zhang; Yanjun Zhang; Tao Lin (Field Crops Research, 2024)

Ordered 2D/3D CoNi-LDH/FeSe electrode for efficient and durable seawater oxidation - Yue Shi; Jiejie Bai; Aixin Ma; Zhitao Zou; Yanru Liu; Haifeng Lin; Dehong Chen; Ruiyong Zhang; Jianping Lai; Lei Wang (Chemical Engineering Journal, 2024)

The value of histopathologic examination and Xpert (MTB/RIF) assay in diagnosis of cervical lymph node tuberculosis after coarse needle biopsy guided by CEUS: a retrospective analysis of 612 cases - Wenzhi Zhang; Jianping Xu; Lin Zhang; Tu Ni (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Objective To investigate the value of histopathological examination (HPE) and Xpert Mycobacterium tuberculosis bacilli/rifampicin (MTB/RIF) assay in diagnosis of cervical lymph node tuberculosis (LN TB) after coarse needle biopsy (CNB). Methods We retrospectively analyzed 612 samples obtained from October 2017 to August 2023 from patients suspected cervical LN TB with surgically pathological, microbial culture confirmed, and clinically confirmed cervical lymph node enlargement who received ultrasound-guided CNB assisted by contrast-enhanced ultrasound (CEUS) at our hospital. All specimens were assessed by HPE and the Xpert (MTB/RIF) assay. We analyzed the results to determine the diagnostic value of HPE and Xpert (MTB/RIF) assay in samples taken after CEUS-assisted CNB of LN TB, and to evaluate the safety of CNB. Results Based on the comprehensive reference standard established in this study, 532 of 612 patients were diagnosed with cervical LN TB, of which 476 were CNB positive cases, the positive rate of diagnosis was 89.5%。The sensitivity, specificity, positive predictive value, negative and predictive value of HPE were 80.4%, 91.2%, 98.4%, 41.2% respectively, while those of the Xpert MTB/RIF assay were 75.7%, 98.7%, 99.7%, 38.0% respectively. No postoperative complications were noted, and the Clavien–Dindo grade was 2. Conclusion CEUS-assisted CNB has high diagnostic value and is safe for cervical LN TB. The sensitivity of HPE is slightly higher than that of Xpert (MTB/RIF) assay, and the specificity of Xpert (MTB/RIF) assay is higher than that of HPE, so Xpert (MTB/RIF) assay can correct the cervical lymph node tuberculosis with negative HPE.

Biomimetic cellulose membrane enables high-performance salinity gradient energy conversion: Coupling surface charge and nanopore structure - Jianping Shi; Kairui Lin; Yuanyuan Liu; Shengyue Niu; Yu Zhang; Weikai Yang; Liulian Huang; Jianguo Li; Lihui Chen (Chemical Engineering Journal, 2024)

Effects of disposable face mask microplastics on soil properties and microbial communities - Liping Lin; Gongren Hu; Yangzi Lijin; Luowei Gan; Ruiqi Zhang; Ling Wang; Changhao Lu; Jianping Gao; Jiatai Lin; Le Yang; Yu Yan; Ruilian Yu (CATENA, 2024)

Multiscale coupling analysis and modeling of airflow and heat transfer for warehouse-packaging-kiwifruit under forced-air cooling - Qian Chen; Jianping Qian; Han Yang; Jiali Li; Xintao Lin; Baogang Wang (Biosystems Engineering, 2024)

Influence of pure sea breeze on urban heat island in Tianjin, China: A perspective from multiple meteorological observations - Mengjiao Shang; Lijuan Cao; Jianping Guo; Zihan Guo; Lin Liu; Shaobo Zhong (Atmospheric Research, 2024)

Mitigating gut immune adverse effects in CTLA-4 blockade for antitumor efficacy - Shijun He; Jianping Zuo; Zemin Lin (Science China Life Sciences, 2024)

Linarin Ameliorates Restenosis After Vascular Injury in Type 2 Diabetes Mellitus via Regulating ADAM10-Mediated Notch Signaling Pathway - Aihua Jiang; Lin Liu; Jianping Wang; Yinglan Liu; Shanshan Deng; Tao Jiang (Cardiovascular Toxicology, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

Delineation of urban growth boundary based on FLUS model under the perspective of land use evaluation in hilly mountainous areas - Yunping Zhang; Jianping Lin; Yimin Huang; Zebin Chen; Chenhui Zhu; Hao Yuan (Journal of Mountain Science, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Physical drivers of Noctiluca scintillans (Dinophyceae) blooms outbreak in the northern Taiwan Strait: A numerical study - Zhonghao Lin; Peng Zhan; Jianping Li; Jun Sasaki; Zhongfeng Qiu; Chun Chen; Shuangyan Zou; Xiaotong Yang; Haifeng Gu (Harmful Algae, 2024)

Recent progress in the efficacy of algal saccharides on skin repair - Yuansen Liu; Yi Zhu; Quanxing Zheng; Hongliang Lu; Huafa Huang; Jianping Zhang; Zhengzhong Fang; Ling Lin; Pengfei Ma (Algal Research, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

The underappreciated role of fugitive VOCs in ozone formation and health risk assessment emitted from seven typical industries in China - Zhiling Liang; Yunjiang Yu; Bingbing Sun; Qian Yao; Xihua Lin; Yongsheng Wang; Jianping Zhang; Yingzi Li; Xuefeng Wang; Zhengzheng Tang; Shexia Ma (Journal of Environmental Sciences, 2024)

Delaying First Fertilization Time Improved Yield and N Utilization Efficiency on Direct Seeding Rice - Yang Li; Xiaolong Yang; Zuolin Zhang; Yiyue Lin; Benfu Wang; Zhisheng Zhang; Changyan Liu; Jianping Cheng (Journal of Plant Growth Regulation, 2024)

Reducing sweetness expectation in milk tea by crossmodal visuo-auditory interaction - Xin Lin; Yujia Liu; Jianping Huang (Appetite, 2024)

Contrasting lake changes in Tibet revealed by recent multi-modal satellite observations - Jiangjun Ran; Lin Liu; Guoqing Zhang; C.K. Shum; Jiahui Qiu; Ruigang Hu; Jianping Li; Junhuan Peng; Cheinway Hwang; Yi Luan; Yue Sun; Min Xu; et al. (Science of The Total Environment, 2024)

The variability in CYP3A4 activity determines the metabolic kinetic characteristics of ketamine - Mengfang Li; Qingqing Li; Dan Lin; Xiang Zheng; Lehao Jin; Jianping Cai; Guoxin Hu; Jianchang Qian (Toxicology, 2023)

Disruption of intestinal structure, tight junction complex, immune response and microbiota after chronic exposure to copper in swamp eel (Monopterus albus) - Changgao Lin; Jianping Fu; Lin Liu; Hui Wang; Lili Wei (Fish & Shellfish Immunology, 2023)

Leaf thermal regulation strategies of canopy species across four vegetation types along a temperature and precipitation gradient - Yingying Zhou; Nawatbhrist Kitudom; Sophie Fauset; Martijn Slot; Zexin Fan; Jianping Wang; Weiwei Liu; Hua Lin (Agricultural and Forest Meteorology, 2023)

Complete genome sequence of Paris polyphylla chlorotic mottle virus infecting Paris polyphylla var. yunnanensis in southwest China - Qiongji He; Binghua Chen; Hongying Zheng; Yuhao Cao; Mengyin Hua; Yueyan Yin; Jiejun Peng; Junmin Li; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2023)

Analysis of the driving factors of the change of erosion-deposition in the Minjiang Estuary, Southeast China - Xiaohe Lai; Jianping Jia; Yuebao Hou; Beihan Jiang; Chuan Lin; Xinlu Lin; Pu Xu; Cheng Chen; Jun Jiang; Yan Liu; Wen Wei (Frontiers in Marine Science, 2023)
Understanding the evolution and driving factors of sedimentation and erosion at the mouths of small and medium-sized mountain streams during various periods is essential for regional spatial utilization, development, and sustainable economic growth. This is particularly important when considering the combined impact of climate change and human activities. This paper presents an analysis of the changes in sedimentation and erosion of mouth isobaths and underwater deltas over different periods using nautical chart data (1950-2019) and analyzes the factors driving changes in sedimentation and erosion during different periods from 1950 to 2020 based on the runoff-sediment discharge of the Minjiang River (MR) and extreme climate factors such as typhoons, especially the driving factors that caused a sudden change in the sedimentation and erosion process between 1998 and 2005. The results indicate that runoff-sediment characteristics are crucial in driving sedimentation and erosion changes. In the past 70 years, the underwater delta of the MRE has mainly experienced four stages: deposition (1950-1992) -erosion (1993-1998) -deposition (1998-2011) -erosion (2011-2019). Taking the impoundment operation of the Shuikou Reservoir in 1993 as the node, the sediment load of the Minjiang River into the sea began to decrease sharply, and then the estuary quickly showed a state of erosion. The change of sediment flux into the sea is the main driving factor for the evolution of erosion and deposition in the Minjiang River Estuary (MRE). The critical value of the erosion-deposition transition is about 570.3 × 10 4 t/yr. After the estuary entered a state of erosion in 1993-1998, significant siltation suddenly occurred in 1998-2005. The reason for the siltation in this period may be related to the frequent transit typhoons and flood events in 1998-2005. Therefore, the change of river sediment supply into the sea is the main driving factor controlling the erosion and deposition evolution of the Minjiang River estuary on a long time scale of more than 10 years, which reflects the influence of large-scale human activities on the river and estuary area in the past half century. Extreme climate events are the incentive to adjust the estuary landform in the short term. Extreme climate events will not fundamentally change the process of estuarine geomorphological evolution under the background of sediment supply reduction.

Long non-coding RNA LOC103222771 promotes infection of porcine reproductive and respiratory syndrome virus in Marc-145 cells by downregulating Claudin-4 - Xinxian Wang; Junlong Bi; Chao Yang; Yongneng Li; Ying Yang; Junwen Deng; Lei Wang; Xiaolin Gao; Yingbo Lin; Jianping Liu; Gefen Yin (Veterinary Microbiology, 2023)

Revealing maleic acid role in the preparation of α-hemihydrate gypsum from titanium gypsum through experiments and DFT calculations - Jingwei Du; Lin Tian; Manfu Qi; Chen Zhang; Hongfeng Di; Xiao Zhi; Jianping Zhu (Science of The Total Environment, 2023)

Investigation on reachable domain of contingency return trajectories in the circumlunar flight phase based on interval analysis - Lin Lu; Jianping Zhou; Haiyang Li; Hailian Zhang (Advances in Space Research, 2023)

Complete genome sequence of a novel mitovirus detected in Colocasia esculenta - Mengting Wu; Chanchan Huang; Lin Wang; Bin Ke; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2023)

Subsoiling depth affects the morphological and physiological traits of roots in film-mulched and drip-irrigated cotton - Rensong Guo; Na Zhang; Liang Wang; Tao Lin; Zipiao Zheng; Jianping Cui; Liwen Tian (Soil and Tillage Research, 2023)

Wet bias of summer precipitation in the northwestern Tibetan Plateau in ERA5 is linked to overestimated lower-level southerly wind over the plateau - Tinghai Ou; Deliang Chen; Jianping Tang; Changgui Lin; Xuejia Wang; Julia Kukulies; Hui-Wen Lai (Climate Dynamics, 2023)
The Tibetan Plateau (TP), also called the Third Pole, is considered to be “the world water tower”. The northwestern TP (NWTP), which has an average elevation higher than 4800 m, is an arid region where the summer precipitation is largely overestimated by the ERA5 global reanalysis product. We hypothesize that this wet bias is mainly caused by unrealistic lower-level winds that trigger strong convection over the region; it can be reduced by using a high-resolution regional climate model with a large domain that allows realistically representing interactions between the Westerlies and Asian summer monsoons. Here, downscaling using the Weather Research and Forecasting (WRF) model driven by ERA5 was conducted with a large domain (8°‒50° N, 65°‒125° E) at 9 km for the period 1979‒2019 (WRF9km). Precipitation values from WRF9km and ERA5 were evaluated against satellite observations; compared with ERA5, WRF9km captured the climatological summer precipitation over the NWTP with a much-reduced wet bias. The ERA5 overestimation is mainly caused by excessive convective precipitation, likely linked to strong vertical motions over the NWTP induced by an overestimated lower-level southerly wind.

The deficiency of N6-methyladenosine demethylase ALKBH5 enhances the neurodegenerative damage induced by cobalt - Chunyan Zheng; Guangxia Yu; Qianqian Su; Lingyan Wu; Jianping Tang; Xinpei Lin; Yao Chen; Zhenkun Guo; Fuli Zheng; Hong Zheng; Liqiong Lin; Ying Tang; et al. (Science of The Total Environment, 2023)

Cobalt induces neurodegeneration through FTO-triggered autophagy impairment by targeting TSC1 in an m6A-YTHDF2-dependent manner - Jianping Tang; Fuli Zheng; Xu Liu; Yanjun Li; Zhenkun Guo; Xinpei Lin; Jinfu Zhou; Yu Zhang; Guangxia Yu; Hong Hu; Wenya Shao; Siying Wu; et al. (Journal of Hazardous Materials, 2023)

Combined transcriptomics and metabolomics analysis reveals lipid metabolic disruption in swamp eel (Monopterus albus) under chronic waterborne copper exposure - Lin Liu; Jianping Fu; Qiongying Tang; Hui Wang; Changgao Lin; Lili Wei (Aquatic Toxicology, 2023)

PM2.5 caused ferroptosis in spermatocyte via overloading iron and disrupting redox homeostasis - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Ying Tang; Chang Liu; Yimeng Wang; Jianping Chen; Xiao Jiang; Huan Yang; Lei Sun; Qing Chen; et al. (Science of The Total Environment, 2023)

Ag quantum dots decorated ultrathin g-C3N4 nanosheets for boosting degradation of pharmaceutical contaminants: Insight from interfacial electric field induced by local surface plasma resonance - Zhenzhou Wang; Danqi Wang; Fang Deng; Xinggang Liu; Xibao Li; Xubiao Luo; Yanzhi Peng; Jian Zhang; Jianping Zou; Lin Ding; Longshuai Zhang (Chemical Engineering Journal, 2023)

Adaption of tobacco rattle virus to its solanaceous hosts is related to the codon usage bias of the hosts and that of the viral 16 K gene - Qi Lin; Yuanting Zheng; Yueyan Yin; Yi Chen; Miaomiao Li; Hongying Zheng; Jianping Chen; Fei Yan; Yuwen Lu; Shengchun Xu (European Journal of Plant Pathology, 2023)

Complete nucleotide sequence of hackberry virus A, a tentative member of the genus Waikavirus - Jiajia Weng; Mengting Wu; Zhuangxin Ye; Lin Wang; Bin Ke; Chanchan Huang; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; et al. (Archives of Virology, 2023)

Two new lanostane-type triterpenoids from the fungus Periconia sp. TJ403-rc01 - Weixi Gao; Fengli Li; Shuang Lin; Beiye Yang; Jianping Wang; Jie Cao; Zhengxi Hu; Yonghui Zhang (Natural Product Research, 2023)

Correction to: Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

Estimation of near-surface ozone concentration and analysis of main weather situation in China based on machine learning model and Himawari-8 TOAR data - Bin Chen; Yixuan Wang; Jianping Huang; Lin Zhao; Ruming Chen; Zhihao Song; Jiashun Hu (Science of The Total Environment, 2023)

Integration of adsorption and simultaneous heterogeneous catalytic oxidation by defective CoFe2O4 activated peroxymonosulfate for efficient As(III) removal: Performance and new insight into the mechanism - Ziqun Lin; Fang Deng; Wei Ren; Zhongbing Wang; Xiao Xiao; Penghui Shao; Jianping Zou; Xubiao Luo (Chemical Engineering Journal, 2023)

The linear behavior of the joint initial-boundary-value predictability of the climate system - Jianlin Yong; Shaoqing Zhang; Zhengyu Liu; Yang Gao; Lixin Wu; Jianping Li; Lv Lu; Yingjing Jiang; Xiaolin Yu; Mingkui Li; Haoran Zhao; Xiaopei Lin (Climate Dynamics, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Complete genome sequence of iris potyvirus B infecting Lilium lancifolium in China - Qi Lin; Dankan Yan; Mengying Hua; Yueyan Yin; Hongying Zheng; Jianping Chen; Fei Yan; Jiejun Peng; Qiongji He; Yuwen Lu (Archives of Virology, 2022)

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

Icariin protects bone marrow mesenchymal stem cells in aplastic anemia by targeting MAPK pathway - Shu Deng; Yuqing Zeng; Jingjing Xiang; Shengyun Lin; Jianping Shen (Molecular Biology Reports, 2022)

A new abietane-type diterpenoid and a new long-chain alkenone from fungus Daldinia sp. TJ403-LS1 - Shuang Lin; Xueke Zhang; Ling Shen; Shuyuan Mo; Junjun Liu; Jianping Wang; Zhengxi Hu; Yonghui Zhang (Natural Product Research, 2022)

Complete genome sequence of a putative novel ilarvirus isolated from Eleocharis dulcis - Lanqing Lv; Xinyang Wu; Jiajia Weng; Yuchao Lai; Kelei Han; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; et al. (Archives of Virology, 2021)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Artemisinin analogue SM934 protects against lupus-associated antiphospholipid syndrome via activation of Nrf2 and its targets - Zemin Lin; Yuting Liu; Li Chen; Shiqi Cao; Yueteng Huang; Xiaoqian Yang; Fenghua Zhu; Wei Tang; Shijun He; Jianping Zuo (Science China Life Sciences, 2021)

Meta-analyses of maternal exposure to atmospheric particulate matter and risk of congenital anomalies in offspring - Guangxia Yu; Yao Chen; Jianping Tang; Zhifeng Lin; Fuli Zheng; Chunyan Zheng; Jinfu Zhou; Qianqian Su; Siying Wu; Huangyuan Li (Environmental Science and Pollution Research, 2021)

Ambient climate determines the directional trend of community stability under warming and grazing - Peipei Liu; Wangwang Lv; Jianping Sun; Caiyun Luo; Zhenhua Zhang; Xiaoxue Zhu; Xingwu Lin; Jichuang Duan; Guangping Xu; Xiaofeng Chang; Yigang Hu; Qiaoyan Lin; et al. (Global Change Biology, 2021)
Changes in ecological processes over time in ambient treatments are often larger than the responses to manipulative treatments in climate change experiments. However, the impacts of human‐driven environmental changes on the stability of natural grasslands have been typically assessed by comparing differences between manipulative plots and reference plots. Little is known about whether or how ambient climate regulates the effects of manipulative treatments and their underlying mechanisms. We collected two datasets, one a 36‐year long‐term observational dataset from 1983 to 2018, and the other a 10‐year manipulative asymmetric warming and grazing experiment using infrared heaters with moderate grazing from 2006 to 2015 in an alpine meadow on the Tibetan Plateau. The 36‐year observational dataset shows that there was a nonlinear response of community stability to ambient temperature with a positive relationship between them due to an increase in ambient temperature in the first 25 years and then a decrease in ambient temperature thereafter. Warming and grazing decreased community stability with experiment duration through an increase in legume cover and a decrease in species asynchrony, which was due to the decreasing background temperature through time during the 10‐year experiment period. Moreover, the temperature sensitivity of community stability was higher under the ambient treatment than under the manipulative treatments. Therefore, our results suggested that ambient climate may control the directional trend of community stability while manipulative treatments may determine the temperature sensitivity of the response of community stability to climate relative to the ambient treatment. Our study emphasizes the importance of the context dependency of the response of community stability to human‐driven environmental changes.

The Significant Role of Radiosonde-measured Cloud-base Height in the Estimation of Cloud Radiative Forcing - Hui Xu; Jianping Guo; Jian Li; Lin Liu; Tianmeng Chen; Xiaoran Guo; Yanmin Lyu; Ding Wang; Yi Han; Qi Chen; Yong Zhang (Advances in Atmospheric Sciences, 2021)

Estimation and Long-term Trend Analysis of Surface Solar Radiation in Antarctica: A Case Study of Zhongshan Station - Zhaoliang Zeng; Zemin Wang; Minghu Ding; Xiangdong Zheng; Xiaoyu Sun; Wei Zhu; Kongju Zhu; Jiachun An; Lin Zang; Jianping Guo; Baojun Zhang (Advances in Atmospheric Sciences, 2021)

Whole brain volume and cortical thickness abnormalities in Wilson’s disease: a clinical correlation study - Yukun Song; Lin Zou; Jing Zhao; Xiangxue Zhou; Yingqian Huang; Haishan Qiu; Haiwei Han; Zhiyun Yang; Xunhua Li; Xiaoying Tang; Jianping Chu (Brain Imaging and Behavior, 2021)

In-Situ Seawater Gamma Spectrometry with LaBr3 Detector at a Nuclear Power Plant Outlet - Daowei Dou; Zhi Zeng; Wen Yu; Ming Zeng; Wu Men; Feng Lin; Hao Ma; Jianping Cheng; Junli Li (Journal of Marine Science and Engineering, 2021)
In a nuclear emergency, the application of in situ spectrometers for monitoring environmental radioactivity is significantly important, as information on the type and activity of radionuclides released from the accident can be obtained quickly. However, in emergency environmental radiological monitoring, a balance between energy resolution and detecting efficiency must be considered in selecting an appropriate detector. In this study, in situ gamma spectrometry was conducted with the LaBr3 detector to determine the radioactivity of seawater at the discharging outlet of a coastal nuclear power plant in southeast China. The results show that the LaBr3 scintillator has excellent energy resolution and detection efficiency, making it a promising detector for emergency monitoring.

Construction of an infectious full-length cDNA clone of potato aucuba mosaic virus - Buyang Chen; Qi Lin; Yueyan Yin; Liangliang Jiang; Fang Wang; Shuzhen Hu; Xinyang Wu; Fei Xu; Jiejun Peng; Hongying Zheng; Chengqi Yan; Xiaohan Mo; et al. (Archives of Virology, 2021)

Complete genome sequence of passiflora virus Y infecting passion fruit in China - Binghua Chen; Dali Wu; Hongying Zheng; Guangze Li; Yuhao Cao; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2021)

Complete genome sequence of a novel foveavirus isolated from Allium sativum L. in China - Qi Luo; Shuzhen Hu; Qi Lin; Fei Xu; Jiejun Peng; Hongying Zheng; Guanwei Wu; Shaofei Rao; Jianping Chen; Yuwen Lu; Fengling Guo; Fei Yan (Archives of Virology, 2021)

Further data on the levels of emerging Fusarium mycotoxins in cereals collected from Tianjin, China - Xiaohui Lin; Qian Zhang; Yi Zhang; Jianping Li; Mingyue Zhang; Xiao Hu; Fengqin Li (Food Additives & Contaminants Part B-Surveillance, 2021)

Complete genome sequence of a new achyranthes virus A isolate from Achyranthes bidentata in China - Xinyang Wu; Yuchao Lai; Lanqing Lv; Kelei Han; Ziqiang Chen; Yuwen Lu; Jiejun Peng; Lin Lin; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2021)

Benzophenanthridine alkaloids suppress lung adenocarcinoma by blocking TMEM16A Ca2+-activated Cl− channels - Gaohua Zhang; Lin Zhu; Yucong Xue; Zhijun Zhao; Honglin Li; Zhiyun Niu; Xiangchong Wang; Pingping Chen; Jianping Zhang; Xuan Zhang (Pflügers Archiv - European Journal of Physiology, 2020)

Application and verification of a multivariate real-time early warning method for rainfall-induced landslides: implication for evolution of landslide-generated debris flows - Zongji Yang; Liyong Wang; Jianping Qiao; Taro Uchimura; Lin Wang (Landslides, 2020)
Rainfall-induced landslides are a frequent and often catastrophic geological disaster, and the development of accurate early warning systems for such events is a primary challenge in the field of risk reduction. Understanding of the physical mechanisms of rainfall-induced landslides is key for early warning and prediction. In this study, a real-time multivariate early warning method based on hydro-mechanical analysis and a long-term sequence of real-time monitoring data was proposed and verified by applying the method to predict successive debris flow events that occurred in 2017 and 2018 in Yindongzi Gully, which is in Wenchuan earthquake region, China. Specifically, long-term sequence slope stability analysis of the in situ datasets for the landslide deposit as a benchmark was conducted, and a multivariate indicator early warning method that included the rainfall intensity-probability ( I-P ), saturation ( S i ), and inclination ( I r ) was then proposed. The measurements and analysis in the two early warning scenarios not only verified the reliability and practicality of the multivariate early warning method but also revealed the evolution processes and mechanism of the landslide-generated debris flow in response to rainfall. Thus, these findings provide a new strategy and guideline for accurately producing early warnings of rainfall-induced landslides.

Complete Genome of Vibrio neocaledonicus CGJ02-2, An active Compounds Producing Bacterium Isolated from South China Sea - Lin Tan; Isabel Gómez-Betancur; Suxia Guo; Yu Ge; Jianping Zhao; Chang Chen; Nan Wang (Current Microbiology, 2020)

Rehabilitation effect of the combined application of bamboo biochar and coal ash on ion-adsorption-type rare earth tailings - Qin Zhang; Guangyue Wan; Caiyun Zhou; Jie Luo; Jianping Lin; Xiaomin Zhao (Journal of Soils and Sediments, 2020)

Regional eco-efficiency evaluation and spatial pattern analysis of the Yangtze River Economic Zone - Lin Ha; Jianjun Tu; Jianping Yang; Chunhai Xu; Jiaxing Pang; Debin Lu; Zuolin Yao; Wenyu Zhao (Journal of Geographical Sciences, 2020)

Epidemiology, molecular characterization, and recombination analysis of chicken anemia virus in Guangdong province, China - Chen Tan; Zhanxin Wang; Xiaoya Lei; Junpeng Lu; Zhuanqiang Yan; Jianping Qin; Feng Chen; Qingmei Xie; Wencheng Lin (Archives of Virology, 2020)

The response of warm-season precipitation extremes in China to global warming: an observational perspective from radiosonde measurements - Jianping Guo; Yan Yan; Dandan Chen; Yanmin Lv; Yi Han; Xiaoran Guo; Lin Liu; Yucong Miao; Tianmeng Chen; Ji Nie; Panmao Zhai (Climate Dynamics, 2020)

Influence of different fiber types on properties of biocemented calcareous sand - Xuewen Lei; Shengqiang Lin; Qingshan Meng; Xinghua Liao; Jianping Xu (Arabian Journal of Geosciences, 2020)

Comparative analysis of mitochondrial genome of a deep-sea crab Chaceon granulates reveals positive selection and novel genetic features - Bo Zhang; Yingying Wu; Xin Wang; Wei Jiang; Jianping Yin; Qiang Lin (Journal of Oceanology and Limnology, 2020)

Contribution of SST change to multidecadal global and continental surface air temperature trends between 1910 and 2013 - Yidan Xu; Jianping Li; Cheng Sun; Xiaopei Lin; Hailong Liu; Lanning Wang; Yishuang Liang; Qiuyun Wang; Yazhou Zhang; Zhaolu Hou; Fuchang Wang (Climate Dynamics, 2020)
The global mean surface air temperature (GMST) shows multidecadal variability over the period of 1910–2013, with an increasing trend. This study quantifies the contribution of hemispheric surface air temperature (SAT) variations and individual ocean sea surface temperature (SST) changes to the GMST multidecadal variability for 1910–2013. At the hemispheric scale, both the Goddard Institute for Space Studies (GISS) observations and the Community Earth System Model (CESM) Community Atmosphere Model 5.3 (CAM5.3) simulation indicate that the Northern Hemisphere (NH) favors the GMST multidecadal trend during periods of accelerated warming (1910–1945, 1975–1998) and cooling (1940–1975, 2001–2013), whereas the Southern Hemisphere (SH) slows the intensity of both warming and cooling processes. The contribution of the NH SAT variation to the GMST multidecadal trend is higher than that of the SH. We conduct six experiments with different ocean SST forcing, and find that all the oceans make positive contributions to the GMST multidecadal trend during rapid warming periods. However, only the Indian, North Atlantic, and western Pacific oceans make positive contributions to the GMST multidecadal trend between 1940 and 1975, whereas only the tropical Pacific and the North Pacific SSTs contribute to the GMST multidecadal trend between 2001 and 2013. The North Atlantic and western Pacific oceans have important impacts on modulating the GMST multidecadal trend across the entire 20th century. Each ocean makes different contributions to the SAT multidecadal trend of different continents during different periods.

Characterization of a Saccharum spontaneum with a basic chromosome number of x = 10 provides new insights on genome evolution in genus Saccharum - Zhuang Meng; Jinlei Han; Yujing Lin; Yiyong Zhao; Qingfang Lin; Xiaokai Ma; Jianping Wang; Muqing Zhang; Liangsheng Zhang; Qinghui Yang; Kai Wang (Theoretical and Applied Genetics, 2020)

Transcriptome sequencing of Eospalax fontanierii to determine hypoxia regulation of cardiac fibrinogen - Lulu Xu; Zhiqiang Hao; Jinyan Lin; Qiong Zhao; Baojun Zhang; Guanglin Li; Jianping He; Jingang Li (Molecular Biology Reports, 2019)

Molecular evolution and lineage-specific expansion of the PP2C family in Zea mays - Kai Fan; Shuna Yuan; Jie Chen; Yunrui Chen; Zhaowei Li; Weiwei Lin; Yongqiang Zhang; Jianping Liu; Wenxiong Lin (Planta, 2019)

TLR2 gene in seahorse brood pouch plays key functional roles in LPS‐induced antibacterial responses - Bo Zhang; Huixian Zhang; Geng Qin; Yuhong Liu; Xue Han; Jianping Yin; Qiang Lin (Journal of Fish Diseases, 2019)

Declining diurnal temperature range in the North China Plain related to environmental changes - Weitao Xue; Jianping Guo; Yong Zhang; Shunwu Zhou; Yuan Wang; Yucong Miao; Lin Liu; Hui Xu; Jian Li; Dandan Chen; Huan Liu (Climate Dynamics, 2019)

Synoptic patterns and sounding‐derived parameters associated with summertime heavy rainfall in Beijing - Yan Yan; Yucong Miao; Jianping Guo; Shuhua Liu; Huan Liu; Mengyun Lou; Lin Liu; Dandan Chen; Weitao Xue; Panmao Zhai (International Journal of Climatology, 2019)
Heavy precipitation in Beijing is modulated by both synoptic forcings and local thermodynamic characteristics of troposphere, which has yet to be well known. This study investigated the large‐scale synoptic patterns and local sounding features associated with the summertime heavy precipitation in Beijing, based on long‐term surface meteorological observations, radiosonde measurements, in combination of reanalysis data from 2008 to 2017. The results show that the heavy rainfall occurs more frequently in late July, which is associated with the movement of subtropical anticyclone. The sounding parameters during the heavy rainfall days are examined as well. It is found that the heavy rainfall is often related to favourable convective conditions characterized by abundant water vapour and high unstable energy. The soundings for around 45% of heavy rainfall days in Beijing exhibit the pattern of “thin tube” (TT), and those for ~25 and ~20% of heavy rainfall days show the patterns of “loaded gun” (LG) and “inverted V” (IV), respectively. On average, the rainfall amount of TT is 55.8 mm/day, which is ~3 mm/day (~15 mm/day) higher than that of LG (IV). The more frequent and heavier rainfall observed for TT pattern is due to the high values of precipitable water and wind shear. On the large scale, three dominant synoptic patterns associated with heavy rainfall in Beijing have been identified using the T‐mode principle component analysis. These synoptic patterns are all characterized by prevailing southerly winds within the lower troposphere, resulting in water vapours being easily transported from southern regions to Beijing, which in turn favours the occurrence of heavy precipitation. These dominant synoptic patterns and thermodynamic characteristics associated with the heavy rainfall in Beijing revealed in this study have important implications for better understanding of heavy rainfall in the North China Plain.

Precipitable water and CAPE dependence of rainfall intensities in China - Wenhao Dong; Yanluan Lin; Jonathon S. Wright; Yuanyu Xie; Xungang Yin; Jianping Guo (Climate Dynamics, 2019)

Tropopause trend across China from 1979 to 2016: A revisit with updated radiosonde measurements - Xinyan Chen; Jianping Guo; Jinfang Yin; Yong Zhang; Yucong Miao; Yuxing Yun; Lin Liu; Jian Li; Hui Xu; Kaixi Hu; Panmao Zhai (International Journal of Climatology, 2019)
The long‐term trend in tropopause has profound implications for the expansion of tropical zone and the variation of large‐scale circulation. However, the changes of tropopause in China have not been explicitly investigated as yet. In this study, the trend of lapse rate tropopause (LRT) height over China has been comprehensively revisited for the period of 1979–2016, using the newly released quality‐controlled radiosonde data from China Meteorological Administration. Results show that the LRT height in most parts of China shows a significant upwards trend with a rate of 370 m/decade, most likely due to global warming. The fastest increase occurs in northwest region, followed by the low‐latitude regions (15°–25°N), while the slowest increase occurs in the high‐latitude regions (45°–55°N). Overall, the LRT height varies with latitudes, exhibiting a “south high and north low” pattern. In particular, high LRT height over low latitudes is found to be expanding rapidly polewards in recent years, in contrast to almost constant LRT height over mid and high latitudes. In terms of the seasonality, tropopause height reaches the peak in summer and bottom in winter. The frequency distribution in the vertical direction exhibits a bimodal pattern with the major peak mostly occurring at around 15 km and a secondary peak occurring between 8 and 12 km. This bimodal distribution is similar to the findings revealed in previous studies. Our findings offer important circumstantial observational evidence for the polewards expansion of the Tropics under global warming.

Inter‐annual variation of the spring haze pollution over the North China Plain: Roles of atmospheric circulation and sea surface temperature - Shangfeng Chen; Jianping Guo; Linye Song; Jian Li; Lin Liu; Jason Blake Cohen (International Journal of Climatology, 2019)
Haze pollution is a serious air quality issue in China. Previous studies over the North China Plain (NCP) mainly focused on analysing the haze during boreal winter. However, the variation in haze during spring and the related factors remain unclear. This study investigates inter‐annual variation of the spring haze, which is represented by the humidity‐corrected dry extinction coefficient (DEC) over the NCP. During high DEC years, pronounced positive DEC anomalies appear over the NCP and its surrounding regions. Correspondingly, a notable anticyclonic anomaly is observed over Northeast Asia, inducing significant southeasterly wind anomalies over the NCP. The anomalous southeasterly winds reduce wind speed and increase relative humidity, which provides favourable meteorological conditions for accumulation and growth of aerosol pollutants. Further analysis shows that the North Atlantic Oscillation (NAO) contributes to the formation of anticyclonic anomalies over Northeast Asia via downstream propagating atmospheric wave trains. Additionally, positive sea surface temperature (SST) anomalies over the subtropical northeastern Atlantic Ocean may also impact the DEC variation. The linear barotropic model experiment further confirms the important role of subtropical northeastern Atlantic SST anomalies in contributing to the anomalous anticyclone over Northeast Asia and southerly wind anomalies over the NCP region, which are triggered via eastwards propagating atmospheric wave trains. This study gives support to the idea that the NAO and the North Atlantic SST may be potential predictors for the frequently observed springtime NCP haze variation.

Cover Image - Geng Qin; Yuan Zhang; Bo Zhang; Xin Wang; Jianping Yin; Qiang Lin (Journal of Fish Diseases, 2018)

Seahorse TLR 5 gene responses to Vibrio vulnificus infection, which in combination with scuticociliates causes heavy reductions in seahorse aquaculture - Geng Qin; Yuan Zhang; Bo Zhang; Xin Wang; Jianping Yin; Qiang Lin (Journal of Fish Diseases, 2018)

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Declining hailstorm frequency in China during 1961–2015 and its potential influential factors - Wenhui Zhao; Jianping Guo; Zhanyu Yao; Yuxing Yun; Shuo Jia; Weijian Wang; Pei Zhang; Hui Xu; Huan Liu; Liangshu Gao; Yanluan Lin; Mingxin Li; et al. (International Journal of Climatology, 2018)
Based on 55 years (from 1961 to 2015) of ground‐based hailstorm and atmospheric sounding observations, the climatological characteristics of hailstorms in China, along with potential influencing factors, were analysed. We found that hailstorms exhibit large spatial and temporal variability, with the peak occurring in spring in south China, and in summer in north China. The Tibetan Plateau (TTP) is a region with high hailstorm frequency. Overall, the frequency of hailstorms has decreased over the 55 years, although there was an increase from 1961 to 1985. In terms of diurnal variability, while hailstorm frequency peaks in the afternoon in most of China, it peaks during the night or early morning in southwest China. The magnitude of the peak increased during the 1960s and 1970s, and then decreased afterwards. Hailstorms are negatively correlated with daily mean temperature but are positively correlated with diurnal temperature range, convective available potential energy (CAPE) and totals–totals index. The increase of hailstorms during the period from 1961 to 1985 is mainly correlated with the increase in CAPE over the TTP region, while the decrease of hailstorms afterwards is correlated with all four convective parameters. The finding has significant implications for the potential impact of increasing greenhouse gases on climatological changes in hailstorm.

The basic helix–loop–helix transcription factor Crf1 is required for development and pathogenicity of the rice blast fungus by regulating carbohydrate and lipid metabolism - Huijuan Cao; Pengyun Huang; Yuxin Yan; Yongkai Shi; Bo Dong; Xiaohong Liu; Lidan Ye; Fucheng Lin; Jianping Lu (Environmental Microbiology, 2018)
Summary Pyricularia oryzae is a plant pathogen causing rice blast, a serious disease spreading in cultivated rice globally. Transcription factors play important regulatory roles in fungal development and pathogenicity. Here, we characterized the biological functions of Crf1, a basic helix–loop–helix (bHLH) transcription factor, in the development and pathogenicity of P. oryzae with functional genetics, molecular and biochemical approaches. We found that CRF1 is necessary for virulence and plays an indispensable role in the regulation of carbohydrate and lipid metabolism in P. oryzae . Deletion of CRF1 led to defects in utilization of lipids, ethanol, glycerol and L‐arabinose, and down‐regulation of many important genes in lipolysis, β ‐oxidation, gluconeogenesis, as well as glycerol and arabinose metabolism. CRF1 is also essential for peroxisome and vacuole function, and conidial cell death during appressorium formation. The appressorium turgor, penetration ability and virulence in Δ crf1 were restored by supplementation of exogenous glucose. The virulence of Crf1 mutant was also recovered by adding exogenous D‐xylose, but not by addition of ethanol, pyruvate, leucine or L‐arabinose. These data showed that Crf1 plays an important role in the complex regulatory network of carbohydrate and lipid metabolism that governs fungal development and pathogenicity.

Composition and evolution of the lithospheric mantle beneath the interior of the South China Block: insights from trace elements and water contents of peridotite xenoliths - Hui Zhang; Jianping Zheng; Jianggu Lu; Shaokui Pan; Yi Zhao; Abing Lin; Lu Xiang (Contributions to Mineralogy and Petrology, 2018)

Tension force-induced bone formation in orthodontic tooth movement via modulation of the GSK-3β/β-catenin signaling pathway - Yelin Mao; Liangliang Wang; Ye Zhu; Yu Liu; Hongwei Dai; Jianping Zhou; Dechun Geng; Lin Wang; Yong Ji (Journal of Molecular Histology, 2018)

Climatology of cloud-base height from long-term radiosonde measurements in China - Yong Zhang; Lejian Zhang; Jianping Guo; Jinming Feng; Lijuan Cao; Yang Wang; Qing Zhou; Liangxu Li; Bai Li; Hui Xu; Lin Liu; Ning An; et al. (Advances in Atmospheric Sciences, 2018)

Foxo1 Attenuates NaF-Induced Apoptosis of LS8 Cells through the JNK and Mitochondrial Pathways - Juedan Li; Lin Zhao; Xiaomeng Zhao; Peng Wang; Yan Liu; Jianping Ruan (Biological Trace Element Research, 2018)

A new species of Bothropolys and a new record of Lithobius magnitergiferous (Lithobiidae) from the Qinghai-Tibet Plateau, China - Wen Qin; Penghai Qiao; YanGan Huang; Gonghua Lin; Jianping Su; Tongzuo Zhang (Biologia, 2017)

GA-DELLA pathway is involved in regulation of nitrogen deficiency-induced anthocyanin accumulation - Yongqiang Zhang; Zhongjuan Liu; Jianping Liu; Sheng Lin; Jianfeng Wang; Wenxiong Lin; Weifeng Xu (Plant Cell Reports, 2017)

ER-localized adenine nucleotide transporter ER-ANT1: an integrator of energy and stress signaling in rice - Xiangqian Zhang; Xu Zheng; Shanwen Ke; Haitao Zhu; Fang Liu; Zemin Zhang; Xinxiang Peng; Lin Guo; Ruizhen Zeng; Pei Hou; Ziqiang Liu; Suowei Wu; et al. (Plant Molecular Biology, 2016)

Evaluation of Immunosuppressive Activity of Demethylzeylasteral in a Beagle Dog Kidney Transplantation Model - Huimin An; Yu Zhu; Wenping Xu; Yujun Liu; Jianping Zhang; Zongming Lin (Cell Biochemistry and Biophysics, 2015)

Development of an agroinoculation system for full-length and GFP-tagged cDNA clones of cucumber green mottle mosaic virus - Hongying Zheng; Caili Xiao; Kelei Han; Jiejun Peng; Lin Lin; Yuwen Lu; Li Xie; Xiaohua Wu; Pei Xu; Guojing Li; Jianping Chen; Fei Yan (Archives of Virology, 2015)

Detection of pepper mild mottle virus in pepper sauce in China - Jiejun Peng; Bingbin Shi; Hongying Zheng; Yuwen Lu; Lin Lin; Tong Jiang; Jianping Chen; Fei Yan (Archives of Virology, 2015)

Physical‐biological coupling of N 2 fixation in the northwestern S outh C hina S ea coastal upwelling during summer - Run Zhang; Min Chen; Qing Yang; Yuanshao Lin; Huabin Mao; Yusheng Qiu; Jinlu Tong; E. Lv; Zhi Yang; Weifeng Yang; Jianping Cao (Limnology and Oceanography, 2015)
Here, we present the first combined results of N 2 fixation rates ( 15 N 2 assay), dissolved iron (dFe, 14 C assay) in the northwestern South China Sea (NWSCS) coastal upwelling region during summer. Surface N 2 fixation rate ranged between 0.1 nmol N L −1 d −1 and 5.6 nmol N L −1 d −1 (average 1.0 nmol N L −1 d −1 , n = 50) under nonbloom conditions. At a Trichodesmium bloom station, N 2 fixation rate was ∼ 3 orders of magnitude higher. Depth‐integrated N 2 fixation rate ranged between 7.5 μmol N m −2 d −1 and 163.1 μmol N m −2 d −1 (average 46.4 μmol N m −2 d −1 ). Our results indicate that N 2 fixation is unlikely limited by Fe availability in the NWSCS continental waters, instead, the coastal upwelling‐induced combined effects of physical and biological processes may have played a decisive role. With the upwelled cold, dFe‐rich, nutrient‐replete waters, nondiazotrophic phytoplankton growth would be preferentially enhanced while N 2 fixation was hindered due to relative deficiency of phosphate caused by massive phytoplankton utilization in the coastal upwelling. By comparison, N 2 fixation was notably elevated along with decreased PP in the offshore waters, probably due to a shift from P‐deficiency to N‐deficiency. Consistently, the contribution of N 2 fixation to PP (0.01–2.52%) also increased toward the open waters. As a significant external N source, summertime N 2 fixation is estimated to contribute a flux of 1.4 Gmol N to this area under nonbloom conditions. This study adds to the knowledge of N 2 fixation in the rarely studied subtropical coastal upwellings, and highlights the necessity of future comprehensive studies in such highly dynamic environments.

Bilayer Matrix Tablets for Prolonged Actions of Metformin Hydrochloride and Repaglinide - Wei He; Shijing Huang; Chunyan Zhou; Lin Cao; Jing Yao; Jianping Zhou; Guangji Wang; Lifang Yin (AAPS PharmSciTech, 2015)

Risk Evaluation of Selective Renal Arterial Embolization in the Treatment of Delayed Hemorrhage from Renal Artery Pseudoaneurysm After Partial Nephrectomy - Yu Zhu; Yujun Liu; Jianping Zhang; Zongming Lin (Cell Biochemistry and Biophysics, 2014)

Carbon and nitrogen isotopic composition of particulate organic matter and its biogeochemical implication in the Bering Sea - Feng Lin; Min Chen; Jinlu Tong; Jianping Cao; Yusheng Qiu; Minfang Zheng (Acta Oceanologica Sinica, 2014)

A new species of Australobius (Lithobiomorpha: Lithobiidae) from the Qinghai-Tibet Plateau, China - Wen Qin; Gonghua Lin; Xianxian Zhao; Bang Li; Jiuxiang Xie; Huiqin Ma; Jianping Su; Tongzuo Zhang (Biologia, 2014)

Erratum to: Genome-wide analysis of DNA methylation in an APP/PS1 mouse model of Alzheimer’s disease - Lin Cong; Jianping Jia; Wei Qin; Yan Ren; Yongxin Sun (Acta Neurologica Belgica, 2014)

Genome-wide analysis of DNA methylation in an APP/PS1 mouse model of Alzheimer’s disease - Lin Cong; Jianping Jia; Wei Qin; Yan Ren; Yongxin Sun (Acta Neurologica Belgica, 2014)

Metabolic engineering strategies for improving xylitol production from hemicellulosic sugars - Buli Su; Mianbin Wu; Jianping Lin; Lirong Yang (Biotechnology Letters, 2013)

An optimized sericin-1 expression system for mass-producing recombinant proteins in the middle silk glands of transgenic silkworms - Feng Wang; Hanfu Xu; Lin Yuan; Sanyuan Ma; Yuancheng Wang; Xiaoli Duan; Jianping Duan; Zhonghuai Xiang; Qingyou Xia (Transgenic Research, 2013)

A geospatial web portal for sharing and analyzing greenhouse gas data derived from satellite remote sensing images - Hao Lin; Bailang Yu; Zuoqi Chen; Yingjie Hu; Yan Huang; Jianping Wu; Bin Wu; Rong Ge (Frontiers of Earth Science, 2013)

Ternary Complexes with Core-Shell Bilayer for Double Level Targeted Gene Delivery: In Vitro and In Vivo Evaluation - Ying Fan; Jing Yao; Ronghui Du; Lin Hou; Jianping Zhou; Yun Lu; Qinggang Meng; Qiang Zhang (Pharmaceutical Research, 2013)

Quantitative assessment of the influence of PSMA6 variant (rs1048990) on coronary artery disease risk - Hairong Wang; Mei Jiang; Hua Zhu; Qihong Chen; Peihua Gong; Jie Lin; Jide Lu; Jianping Qiu (Molecular Biology Reports, 2013)

Intron retention and 3′-UTR analysis of Arabidopsis Dicer-like 2 transcripts - Qiongji He; Jiejun Peng; Fei Yan; Lin Lin; Yuwen Lu; Hongying Zheng; Hairu Chen; Jianping Chen (Molecular Biology Reports, 2012)

Spatiotemporal profile of N-cadherin expression in the mossy fiber sprouting and synaptic plasticity following seizures - Hua Lin; Yuangui Huang; Yuping Wang; Jianping Jia (Molecular and Cellular Biochemistry, 2011)

Interaction between potyvirus P3 and ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO) of host plants - Lin Lin; Zhaopeng Luo; Fei Yan; Yuwen Lu; Hongying Zheng; Jianping Chen (Virus Genes, 2011)

Temporal and spatial variability of chlorophyll a concentration in Lake Taihu using MODIS time-series data - Yuchao Zhang; Shan Lin; Xin Qian; Qin’geng Wang; Yu Qian; Jianping Liu; Yi Ge (Hydrobiologia, 2011)

Mapping the self-interacting domains of TuMV HC-Pro and the subcellular localization of the protein - Hongying Zheng; Fei Yan; Yuwen Lu; Liying Sun; Lin Lin; Li Cai; Mingsheng Hou; Jianping Chen (Virus Genes, 2011)

Investigating impacts of urban morphology on spatio-temporal variations of solar radiation with airborne LIDAR data and a solar flux model: a case study of downtown Houston - Bailang Yu; Hongxing Liu; Jianping Wu; Wei-Ming Lin (International Journal of Remote Sensing, 2009)

Molecular cloning and characterization of the Dicer-like 2 gene from Brassica rapa - Fei Yan; Jiejun Peng; Yuwen Lu; Lin Lin; Hongying Zheng; Hairu Chen; Jianping Chen; Michael J. Adams (Molecular Biology Reports, 2009)

Identification of novel splice variants of the Arabidopsis DCL2 gene - Fei Yan; Jiejun Peng; Yuwen Lu; Lin Lin; Hongying Zheng; Hairu Chen; Jianping Chen; Michael J. Adams (Plant Cell Reports, 2009)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Improvement of pristinamycin-producing Streptomyces pristinaespiralis by rational screening - Zhihua Jin; Yinlin Lei; Jianping Lin; Peilin Cen (World Journal of Microbiology and Biotechnology, 2006)

Asymmetric reduction of ethyl 4-chloro-3-oxobutanoate to ethyl (R)-4-chloro-3-hydroxybutanoate with two co-existing, recombinant Escherichia coli strains - Ying Liu; Zhinan Xu; Keju Jing; Xiaoxia Jiang; Jianping Lin; Fang Wang; Peilin Cen (Biotechnology Letters, 2005)

Monogenea from the middle Yangtze Valley: Sinomazocraes changjiangensis n. g., n. sp. (Family Mazocraeidae Price, 1936) on a clupeiform fish from Hubei Province, China - Zhang Jianying; Liu Lin; Fang Jianping; Ding Xuejuan (Systematic Parasitology, 2003)